Application of replication-defective West Nile virus vector to non-flavivirus vaccine targets. Issue 12 (2nd December 2017) - Giel-Moloney, Maryann; Vaine, Michael; Zhang, Linong; Parrington, Mark; Gajewska, Beata; Vogel, Thorsten U.; Pougatcheva, Svetlana O.; Duan, Xiaochu; Farrell, Timothy; Ustyugova, Irina; Phogat, Sanjay; Kleanthous, Harry; et al.
ABSTRACT: The RepliVax vaccine platform(RV) is based on flavivirus genomes that are rationally attenuated by deletion. The self-limiting infection provided by RV has been demonstrated to be safe, highly immunogenic and efficacious for several vaccine candidates against flaviviruses. Here respiratory syncytial virus (RSV) F, influenza virus HA, and simian immunodeficiency virus (SIV) Env proteins were expressed in place of either prM-E or C-prM-E gene deletions of the West Nile (WN) virus genome. The resulting RV-RSV, -influenza and -SIV vaccine prototypes replicated efficiently in complementing helper cells expressing the WN structural proteins in trans. Expressed antigens exhibited correct post-translational processing and the RV recombinants were shown to be highly attenuated and immunogenic in mice, eliciting strong antigen-specific antibodies as well as detectable T-cell responses. These data support the utility of RV vectors for development of vaccines against non-flavivirus targets including rabies and HIV.